2013
DOI: 10.1111/1346-8138.12265
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sodium hypochlorite (bleach) baths in patients with moderate to severe atopic dermatitis in Malaysia

Abstract: Staphylococcus aureus is frequently found in patients with atopic dermatitis (AD) and contributes to disease exacerbation. The objective of this study was to evaluate the efficacy and safety of bleach baths as an adjunctive treatment in AD patients. Patients between 2 and 30 years old with moderate to severe AD were enrolled in a prospective, randomized, placebo-controlled study. Patients soaked in diluted bleach or distilled water baths for 10 min, twice a week for 2 months. Efficacy assessments included the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 13 publications
4
61
0
1
Order By: Relevance
“…In 2013, a study in Malaysia revealed that dilute bleach baths performed twice a week for 2 months decreased both AD severity and S. aureus colonization [92]. Although bleach baths have potential to successfully treat AD through clearance of S. aureus, more studies need to be conducted to confirm the current results with or without antibiotic activity.…”
Section: Therapeutic Strategies To Combat S Aureus On Ad Skinmentioning
confidence: 99%
“…In 2013, a study in Malaysia revealed that dilute bleach baths performed twice a week for 2 months decreased both AD severity and S. aureus colonization [92]. Although bleach baths have potential to successfully treat AD through clearance of S. aureus, more studies need to be conducted to confirm the current results with or without antibiotic activity.…”
Section: Therapeutic Strategies To Combat S Aureus On Ad Skinmentioning
confidence: 99%
“…Wong et al [67] performed a 2-month prospective randomized, double-blinded, placebo-controlled study assessing the efficacy of 0.005% sodium hypochlorite baths in 36 patients aged between 2 and 30 years old with uninfected moderate to severe AD. Patients were given either 100mL of 5% sodium hypochlorite (bleach treatment arm) or distilled water (placebo arm) and instructed to add this into 100 L of water.…”
Section: An Updated Review Of Studies Assessing Antiseptic Use In Atomentioning
confidence: 99%
“…Aqueous cream as soap was provided to standardize their bathing regimen. Follow-up was performed at baseline, week 2, week 4, and week 8 (end) of treatment [67]. Response to treatment was assessed using the EASI score, a validated composite score of BSA from four regions (head and neck, upper limbs, trunk and lower limbs) and a physician's assessment of erythema, edema/induration/papulation, excoriation and lichenification on a 4-point scale.…”
Section: An Updated Review Of Studies Assessing Antiseptic Use In Atomentioning
confidence: 99%
See 2 more Smart Citations